Commitment to Excellence in the New: Revival of the Notion of "the Fine” for Comprehension of the Dialogue between Artistic Image and Intellectual Idea in a Modern Architectural Form - Volchok, Yuri (project baikal, 2016)
The revival of the notion of "the fine" has become one of the tasks in the framework of matching historical and theoretical issues related to architectural criticism at the present stage of architectonic thinking integration into the space of a non-linear world perception. 1954 - 1958. These years are a significant landmark in the history of Russian architecture of the Recent Time. There is the established scientific concept that these very years saw the break with the Renaissance tradition. It is really important to restore the real contents of the dialogue between the said tradition and creative aspirations addressing the future which existed in the middle of the 20th century in our country.
Keywords: fine triad; architecture - sculpture - painting; internal structure; perception of the exterior; architectural form; integrity; Grand-Time Architectonics; Recent-time architecture; Renaissance tradition; architectonic creativity